Studi Putusan Nomor 137/Pdt.G/2021/PN Gianyar Tentang Kepemilikan Hak Atas Tanah yang diperoleh Berdasarkan Perjanjian Nominee - Amar, Nazwa Afipa; Rosmidah, Rosmidah; Suhermi, Suhermi (Wajah Hukum, 2025)
The purpose of this study is to determine and analyze the rights of land owners due to nominee agreements in Decision Number 137/Pdt.G/2021/PN Gianyar and the legal remedies of land owners due to nominee agreements. The problems discussed include: (1) What are the rights of land owners due to nominee agreements after Decision Number 137/Pdt.G/2021/PN Gianyar? (2) What are the legal remedies of land owners due to nominee agreements after Decision Number 137/Pdt.G/2021/PN Gianyar. The method used in this study is normative juridical (case study). The results of the study indicate that the parties to the land lost their rights because the nominee agreement which was the basis for the purchase of the disputed land was contrary to statutory regulations, namely Article 1320 of the Civil Code and the UUPA, and efforts to resolve disputes were through mediation.